Inhibition of Bruton’s tyrosine kinase as a therapeutic strategy for chemoresistant oral squamous cell carcinoma and potential suppression of cancer stemness - Liu, Shao-Cheng (Oncogenesis, 2021)
Locally advanced oral squamous cell carcinoma (OSCC) requires multimodal therapy, including surgery and concurrent chemoradiotherapy (CCRT). CCRT-resistant and recurrent cancer has a poor prognosis. We investigated the effects of Bruton’s tyrosine kinase (BTK) on CCRT-resistant OSCC tissues. The effect of ibrutinib, a first-in-class BTK inhibitor, was tested on stem cell-like OSCC tumorspheres. A tissue array was constructed using tissue samples from 70 patients with OSCC. Human OSCC cell lines, SAS, TW2.6 and HSC-3, were examined. Wound healing, Matrigel invasion, and tumorsphere formation assays, as well as immunofluorescence analysis and flow cytometry, were used to investigate the effects of BTK knockdown (shBTK), ibrutinib, cisplatin, and ibrutinib/cisplatin combination on OSCC cells. We demonstrated that BTK was aberrantly highly expressed in the clinical CCRT-resistant OSCC tissue array, which resulted in poor overall survival in our local Tri-Service General Hospital and freely accessible TCGA OSCC cohorts. shBTK significantly downregulated the stemness markers Nanog, CD133, T cell immunoglobulin-3 (TIM-3), and Krüppel-like factor 4 (KLF4) in SAS tumorspheres and attenuated OSCC cell migration and colony formation. Ibrutinib reduced the number of aldehyde dehydrogenase (ALDH)-rich OSCC cells and reduced tumorsphere formation, migration, and invasion in a dose-dependent manner. Compared with ibrutinib or cisplatin monotherapy, the ibrutinib/cisplatin combination significantly reduced the formation of ALDH + OSCC tumorspheres and enhanced apoptosis. These results demonstrate that ibrutinib effectively inhibits the CSCs-like phenotype of OSCC cells through dysregulation of BTK/CD133 signaling. The ibrutinib/cisplatin combination may be considered for future clinical use.